Into the savage country - Burke, Shannon (Pantheon Books, 2015)
"When the young William Wyeth leaves St. Louis for a fur-trapping expedition, he nearly loses his life and quickly discovers the depth of loyalty among the men who must depend on one another to survive. While convalescing, he falls in love with proud Alene, a young widow who may or may not wait for him. And on a wildly risky expedition into Crow territory, Wyeth finds himself unwittingly at the center of a deadly boundary dispute among Native American tribes, the British government, and American trapping brigades"--Dust jacket flap.